Disappeared supramolecular isomer reappears with perylene guest - In-Hyeok Park; Atanu Dey; Kenta Sasaki; Masaaki Ohba; Shim Sung Lee; Jagadese J. Vittal (IUCrJ, 2020)
Among different types of polymorphism, disappearing polymorphism deals with the metastable kinetic form which can not be reproduced after its first isolation. In the world of coordination polymers (CPs) and metal–organic frameworks (MOFs), despite the fact that many types of supramolecular isomerism exist, we are unaware of disappearing supramolecular isomerism akin to disappearing polymorphism. This work reports a MOF with dia topology that could not be reproduced, but subsequent synthesis yielded another supramolecular isomer, a double-pillared-layer MOF. When perylene was added in the same reaction, the disappeared dia MOF reappeared with perylene as a guest in the channels. Interestingly, the photoluminescence of the dia MOF with a perylene guest is dominated by the emission of the guest molecule. The influence of guest molecules on the stabilization of the supramolecular isomers of a MOF opens up a strategy to access MOFs with different structures.